Experiences of Instructors in Online Teaching: A Phenomenological Study - Baluyos, Genelyn; Clarin, Ariel R. (EduLine: Journal of Education and Learning Innovation, 2021)
The abrupt shift to online distance education as a result of COVID-19 pademic resulted to the diversification of teaching modalities and pedagogies. This study explored the lived experiences of instructors in online teaching during the SY 2020-2021 using Van Manen's hermeneutic phenomenological design. Purposive sampling was used to select the twenty-five participants for the study. In-depth face-to-face interviews were conducted with all the participants to gather information from the teachers. Data analysis was employed using the six components of hermeneutic phenomenological design and with the aid of NVivo software. Results revealed that the instructors’ experiences in online teaching were identified in five themes: preparation of learning materials, realization of learning outcomes, stability of internet connection, availability of technological resources, and difficulty in the conduct of assessment activities. The instructors encountered positive and negative experiences in online teaching. Online teaching enhancement program is recommended in this study.